Michael Riffaterre’s Semiotic Analysis of the Poem ’Ila Ummi’ by Mahmoud Darwish - Faizun, Mochammad; Kawa, Andrew Dedita Dwiki (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
يهدف هذا البحث إلى دراسة القصيدة إلى أمي لمحمود درويش باستخدام نظرية سيميائية لريفاتير. درويش من أحد الشعراء ولد في فلسطين. وقصيدته إلى أمي تحكي عن حنينه لأمه. كلمة الأم في هذه القصيدة يمكن أن نفسرها بالأم البيولوجية التي ولدته والأم باعتبارها المكان الذي نشأ فيه أي وطنه. وهذان المعنيان المحتملان نفسرها من خلفية كتابة القصيدة. ولإثبات هذه الفرضية سيتم فحص القصيدة باستخدام النظرية السيميائية لريفاتير. يستخدم هذا البحث أساليب البحث المكتبي مع تحليل البيانات باستخدام تقنيات الوصفية النوعية. فإن سيميائية لريفاتير تبحث أيضًا عن الهيبوغرامات (Hipogram)، فهي مناسبة لتفسير القصيدة. وتظهر نتائج البحث أن هذه القصيدة هي في الأساس تعبير عن الحزن والشوق والاكتئاب. ويوصف هذا التعبير بأنه حنينه إلى أمه البيولوجية، والتي يمكن تفسيرها أيضاً على أنها وطنه، مدينة ميلاده، أي فلسطين. وفي نفس الوقت فإن نقش هذه القصيدة عندما عاش محمود درويش عام 1965 في أحد السجون في إسرائيل وهيبروغرام من هذه القصيدة هي قصيدة أمي لعبد الله البردوني. Abstract This article explores the poem "Ila Ummi" by Mahmoud Darwish through the lens of Riffaterre’s semiotic theory. Darwish, a prominent Palestinian poet, penned this poem expressing his deep longing for his mother. The word "mother" in the poem carries a twofold significance: it refers both to the biological mother who gave birth to him and to the symbolic motherland, Palestine, the place where he was nurtured. This dual interpretation is informed by the socio-historical context surrounding the poem’s creation. To substantiate this hypothesis, the poem is analyzed using Riffaterre’s semiotic framework. The research methodology employs a desk research approach, with data analysis utilizing qualitative descriptive techniques. Riffaterre’s semiotics also seeks to identify hypograms, hidden textual patterns, which enrich the interpretation of the poem. The research findings reveal that the poem serves as a poignant expression of sadness, longing, and profound grief. This sentiment is rooted in Darwish’s yearning for his biological mother, which simultaneously echoes his longing for his homeland, Palestine, specifically the city of his birth. It is noteworthy that the poem was written in 1965 while Darwish was imprisoned in Israel, adding a layer of subtext to its emotional resonance. Furthermore, the hypogram identified within the poem is "My Mother" by Abdullah Al-Baradouni, hinting at intertextual influences and shared themes of maternal and patriotic longing.